PENGARUH PEMANFAATAN TEKNOLOGI DAN ORIENTASI KEWIRAUSAHAAN TERHADAP KETAHANAN BISNIS PADA USAHA SANJAI DI KOTA BUKITTINGGI - Latifah Sakinah; Yuhendri Leo Vrista (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
The purpose of this study was to examine the effect of technology utilization and entrepreneurial orientation on the business resilience of Sanjai enterprises in Bukittinggi City. The research problem addressed in this study is the relatively low level of technology utilization and entrepreneurial orientation among Sanjai business owners in responding to competition and changes in the business environment. This study employed a quantitative approach with a causal research design. The population consisted of Sanjai business owners in Bukittinggi City, and a total of 85 respondents were selected using the total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS version 23. The results showed that technology utilization and entrepreneurial orientation simultaneously had a significant effect on business resilience. Partially, technology utilization did not have a significant effect on business resilience, whereas entrepreneurial orientation had a significant effect on the business resilience of Sanjai enterprises. These findings imply that strengthening entrepreneurial orientation and optimizing the use of technology are essential for enhancing the business resilience of Sanjai enterprises in Bukittinggi City.